ANALISIS SUBSIDI BENIH, PRODUKSI, DAN PRODUKTIVITAS JAGUNG DI JAWA TIMUR - Nurasa, SoTjetjep; Muslim, Chairul (Lampung University)
The objective of this study is to determine the eligibility of corn seed subsidy and to investigate impact of seed utilization on productivity, cost and revenue of corn farming. The study employs integration index to determine stage operation of seed company as well as cost revenue analysis to understand the ratio between revenue and cost. The study shows that the reason farmer use certified seeds is related to expectation that the seed will give higher yield (30%) as tt shows by the relative higher productivity in which farming with certified seed produce 5000 kg/ha where as non certified seed produced 4000/ha. Ratio of return to revenue for certified seed farming is 1,82 while 1,57 for non certified farming. The integration index shows that PT. SHS Company has high integration leading to provide higher added value. However, the role multinational corporation in seeds market is dominant leaving domestic company far behind. This suggests that seeds market is very lucrative business in Jawa Timur.